Keratinocyte Growth Factor (KGF) Modulates Epidermal Progenitor Cell Kinetics through Activation of p63 in Middle Ear Cholesteatoma - Yamamoto-Fukuda, Tomomi (J Assoc Res Otolaryngol, 2018)
The basal stem/progenitor cell maintains homeostasis of the epidermis. Progressive disturbance of this homeostasis has been implicated as a possible cause in the pathogenesis of epithelial disease, such as middle ear cholesteatoma. In many cases of stem/progenitor cell regulation, the importance of extracellular signals provided by the surrounding cells is well-recognized. Keratinocyte growth factor (KGF) is a mesenchymal-cell-derived paracrine growth factor that specifically participates in skin homeostasis; however, the overexpression of KGF induces middle ear cholesteatoma. In this study, two kinds of thymidine analogs were transferred at different time points and we investigated the effects of overexpressed KGF on the cell kinetics of stem/progenitor cells in vivo. As a result, BrdU(+)EdU(+) cells (stem/progenitor cells) were detected in the thickened epithelium of KGF-transfected specimens. The use of a high-resolution microscope enabled us to analyze the phosphorylated level of p63 in individual nuclei, and the results clearly demonstrated that BrdU(+)EdU(+) cells are regarded as progenitor cells. In the overexpression of KGF, the stimulation of progenitor cell proliferation was inhibited by SU5402, an inhibitor for tyrosine kinase of KGFR. These findings indicate that KGF overexpression may increase stem/progenitor cell proliferation and block terminal differentiation, resulting in epithelial hyperplasia, which is typical in middle ear cholesteatoma.